2001
DOI: 10.1016/s0304-3959(01)00350-5
|View full text |Cite
|
Sign up to set email alerts
|

Contingent negative variation in subjects at risk for migraine without aura

Abstract: Migraine is a complex disease with a significant genetic background. One possible strategy to investigate the genetics of migraine is the evaluation of functional vulnerability markers or biological elementary endophenotypes in individuals with the greatest probability of developing the disorder (high-risk design). In this study the contingent negative variation (CNV) was recorded in 35 high-risk subjects with a positive family history of migraine without aura (FHP), 35 low-risk individuals without a positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 40 publications
5
51
0
Order By: Relevance
“…It was found that both topiramate and levetiracetam were efficacious, with respect to placebo, in reducing headache frequency to almost 50% of the basal one. In basal conditions, the loss of CNV habituation and the hypersynchronization of alpha rhythm under repetitive flash stimulation were confirmed in this migraine series compared with controls [Siniatchkin et al, 2001;Angelini et al, 2004]. The clinical efficacy of both AEDs was correlated significantly with their normalizing effect on CNV habituation (see Fig.…”
Section: Recent Evidence About the Neurophysiologic Effects Of Aed Insupporting
confidence: 67%
See 1 more Smart Citation
“…It was found that both topiramate and levetiracetam were efficacious, with respect to placebo, in reducing headache frequency to almost 50% of the basal one. In basal conditions, the loss of CNV habituation and the hypersynchronization of alpha rhythm under repetitive flash stimulation were confirmed in this migraine series compared with controls [Siniatchkin et al, 2001;Angelini et al, 2004]. The clinical efficacy of both AEDs was correlated significantly with their normalizing effect on CNV habituation (see Fig.…”
Section: Recent Evidence About the Neurophysiologic Effects Of Aed Insupporting
confidence: 67%
“…Multi-modal evoked potentials have shown this defect in habituation [Ambrosini et al, 2003], including those specifically evoked by nociceptive fiber stimulation [Valeriani et al, 2003;. One of the most reliable indicators of migraine predisposition is the increased amplitude of an event-related potential, the contingent negative variation (CNV), caused by reduced habituation [Schoenen and Timsit-Berthier, 1993]: the CNV amplitude and habituation normalize before an attack [Kropp and Gerber, 1998] and its abnormal pattern appears to be a marker of genetic susceptibility for migraine [Siniatchkin et al, 2001.…”
Section: Neurophysiologic Patterns In Migrainementioning
confidence: 99%
“…In migrainous child-parent pairs, habituation of evoked potentials has a clear familial pattern. 66,71 Moreover, in asympto matic individuals who have a first degree relative with migraine, and are thus at risk of developing migraine during their lifetime, cortical evoked potentials 79 and nociceptive blink reflexes 86 (nBRs, discussed under processing of noxious stimuli below) showed amplitude and habituation abnormalities similar to those found interictally in people with migraine.…”
Section: Possible Mechanisms Of Habituationmentioning
confidence: 92%
“…For instance, cortical responsivity is cyclic in individuals with migraine, 71 and varies in parallel with changes in platelet serotonin content. 73 The period icity of neurophysiological brain activity might also be related to psychophysical, genetic 66,79 or metabolic factors, 80 or to the biorhythms of hypothalamic activity. 81 Migraine periodicity might thus be the result of several inter acting biological cycles.…”
Section: Episodic Migrainementioning
confidence: 99%
“…Disease duration also had an effect on CNV abnormalities in migraineurs [88]. A strong familial influence on CNV parameters was reported by Siniatchkin et al [89], who found abnormalities not only in migraineurs but also in healthy subjects with a positive family history for migraine [90]. The sensitivity of CNV to different prophylactic agents used in migraine and the relative specificity of the difference between headache forms suggest that CNV is a useful method for studying headaches [91].…”
mentioning
confidence: 92%